Website Design Innovation Strategy for Brand XYZ Using the Design Thinking Approach - Haifa Sausan; Ellya Zulaikha (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2025)
The rapid growth of e-commerce in Indonesia has transformed consumer behavior and increased expectations for seamless digital shopping experiences. Despite Brand XYZ’s popularity on social media and marketplaces, its official website performed poorly due to unintuitive navigation, outdated visuals, and inefficient checkout processes. This study applies the Design Thinking methodology, combined with the American Customer Satisfaction Index (ACSI), to redesign the Brand XYZ website. Qualitative data were gathered through empathy mapping, user journey analysis, and value proposition canvases, while quantitative data were measured using pre-test and post-test ACSI surveys. The SCAMPER method was used during the ideation stage to generate solution concepts, which were translated into prototypes using Figma and tested for usability. Results indicate a substantial improvement in satisfaction, with ACSI scores increasing from 44.42 (pre-test) to 80.53 (post-test). Key gains include simplified navigation, mobile responsiveness, consistent brand identity, and a streamlined three-step checkout. The findings confirm that integrating Design Thinking with ACSI provides a comprehensive framework for addressing usability and brand perception challenges in fashion e-commerce.